1989
DOI: 10.1111/j.1469-8137.1989.tb02395.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phytopathogenic fungi in vitro by cell free culture media of ectomycorrhizal fungi

Abstract: S U M M A R \The cell free culture media of 16 ectomycorrhizal funj^i were tested for their abiht\-to inhibit the growth of 23 phytopatho^ens and one eetomycorrhizal fungus. I'^xtracelkilar metabolites of se\-en (44",,) ectomyeorrhizal funsji, Amanita citrina, Lncraria bicoloy, haciaria laecaUi, Pisohthits tnutorius, Suillus bm'ipes, TriclioloiiKi ftcwoiireiis ai-idTriclwloina pessiindatum, inhibited the f^rowth ol up to 20 of 24 (83 ",,) funjji tested. Two ectomycorrhizal fungi, P. tinctorius and T. pessundat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 22 publications
3
15
0
2
Order By: Relevance
“…13). Kope and Fortin (1990) revealed much variation in basidiospore spine morphology of various provenances. Monokaryotic cultures of the four mating types of the two isolates were paired and were found to be not compatible.…”
Section: Microscopic Studiesmentioning
confidence: 99%
“…13). Kope and Fortin (1990) revealed much variation in basidiospore spine morphology of various provenances. Monokaryotic cultures of the four mating types of the two isolates were paired and were found to be not compatible.…”
Section: Microscopic Studiesmentioning
confidence: 99%
“…It has been shown that mycorrhizal fungi have the enzymatic capacity to degrade a range of organic compounds (Leake & Read, 1997) and that some species may make limited use of more recalcitrant components such as fungal cell-wall material (Dighton et al, 1987 ;Leake & Read, 1990 ;Kerley & Read, 1995. It has also been shown that substances produced by mycorrhizal fungi can induce hyphal lysis in a range of phytopathogenic fungi (Kope & Fortin, 1989. Lysis of saprotrophic hyphae is not necessarily a result of combative activity of the mycorrhizal fungi.…”
Section: mentioning
confidence: 99%
“…Essas associações melhoram a capacidade de absorção e utilização dos nutrientes (Bougher et al, 1990;Thomson et al, 1994), de absorção de água (Levy & Krikun, 1980), de tolerân-cia a condições desfavoráveis do solo (Wilkins, 1991) e de resistência a microrganismos patogênicos ou deletérios (Marx, 1969;Kope & Fortin, 1989;Newsham et al, 1995).…”
Section: Introductionunclassified